Circulating levels of DLK1 and glucose homeostasis in girls with obesity: A pilot study - Palumbo, Stefania; Umano, Giuseppina Rosaria; Aiello, Francesca; Cirillo, Grazia; Miraglia del Giudice, Emanuele; Grandone, Anna (Frontiers in Endocrinology, 2022)
Introduction DLK1 gene is considered a molecular gatekeeper of adipogenesis. DLK1 mutations have been reported as a cause of central precocious puberty associated with obesity and metabolic syndrome with undetectable DLK1 serum levels. We investigated the association between DLK1 circulating levels with clinical and biochemical parameters in obese adolescents and healthy controls. Methods Sixty-five obese adolescents and 40 controls were enrolled and underwent a complete clinical examination and biochemical assessment for glucose homeostasis and DLK1 plasma levels. Results We observed lower DLK1 levels in cases compared to controls. Moreover, we found a negative correlation between DLK1 and HOMA-IR and a direct correlation with insulin-sensitivity index. Discussion Our findings suggest that DLK1 might be involved in metabolic derangement in obese children.